Understanding adherence experience of hypertensive patients referred for counselling at a public health clinic - Lee, Khuan (2012)
This study aims to understand the experience of hypertensive patients in adhering to medicine. Despite the availability of effective medicine, non-adherence to medicine has been identified as the main cause of failure in controlling hypertension.Adherence is a complex phenomenon that affects not only the health of the patients but also their entire lives. The research gap in this field is the absence of the patients’perspective and a dearth of qualitative research. The researcher adopted the Abductive Research Strategy (ARS), which emphasized on postmodern epistemology-social constructionism to explore the social world of participants and generate social scientific knowledge through abducting participants’ accounts. Four research questions were designed to investigate the adherence experience of the patients: 1) What are the psychological responses of patients after being diagnosed as hypertensive? 2) How do patients perceive the medicine prescribed for them? 3)What types of adherence behaviour do patients engage in? 4) Why do patients engage in a particular type of adherence behaviour? The researcher purposively selected 26 participants from a public health clinic in Selangor, Malaysia. After obtaining ethical committee clearance, the researcher interviewed participants through in-depth semi-structured interviews lasting between one and two hours for three sessions on different dates. The interviews were recorded and transcribed verbatim. NVivo 7 was used to organise the data and the data were analysed by using the constant comparison method to produce typologies. The rigour and trustworthiness of the study was achieved through prolonged engagement,member checking, non-participant observation, review of documents, field notes,peer examination and audit trail. The findings demonstrated that psychological responses undergone by participants after being diagnosed with hypertension were divided into emotional and cognitive responses. Sub-types of emotional response include anxiety, denial, depression, and acceptance, while cognitive sub-types comprise the justification of illness causation through which patients rationalize their illness as being caused by the risk factors of hypertension, self-inflicted, change of environment, emotional stress and personality. Participants are presented with six types of perception of medicine – positive perception to Western Medicine (WM), negative perception to WM, positive perception of Complementary and Alternative Medicine (CAM), negative perception of CAM, positive versus negative perception to WM and positive versus negative perception to CAM. Three types of adherence behaviour were found including faithful adherence, self-regulating and intentional non-adherence. Participants follow medicine faithfully because of fear of death and disease complications, positive perception towards medicine, social support, good relationship with doctor and limited choices. Participants self-regulate their medicine because of the side effects of medicine, adapted to treatment, influence of cultural and lay knowledge as well as avoid not being treated by the doctor. Intentional non-followers do not take medicine due to the absence of the symptoms of illness as well as communication and language barrier. In summary, adherence to medicine is a multifactorial and value-laden type of behaviour. Likewise, patient is not a passive follower of the medicine prescribed. Therefore, to improve adherence to the prescribed medicine in ypertension, the counsellor should use patient-centred counselling approaches to encourage selfmanagement in long-term treatment. Thus, cognitive behavioural therapy and post modern approach –narrative therapy was suggested for counsellors to utilize in the process of helping and understanding the clients. The understanding of clients’ experience could assist counsellor in decision-making and improve the quality of counselling services.